Transverse Myelitis Following SARS‐CoV‐2 Vaccination: A Pharmacoepidemiological Study in the World Health Organization's Database. Issue 6 (23rd September 2022) - Nguyen, Sophie; Bastien, Etienne; Chretien, Basile; Sassier, Marion; Defer, Gilles; Nehme, Ahmad; Lelong‐Boulouard, Véronique; Alexandre, Joachim; Fedrizzi, Sophie; Morice, Pierre‐Marie
Abstract : Background: Transverse myelitis (TM) has recently been associated by health authorities with Ad26.COV2.S (Janssen/Johnson & Johnson), one of the 5 US Food and Drug Administration (FDA) or European Medicines Agency (EMA) labeled severe acute respiratory syndrome‐coronavirus 2 (SARS‐CoV‐2) vaccines. It is unknown whether a similar association exists for the other FDA or EMA labeled SARS‐CoV‐2 vaccines (BNT162b2 [Pfizer/BioNTech], mRNA‐1273 [Moderna], ChAdOx1nCov‐19 [Oxford–AstraZeneca], and NVX‐CoV2373 [Novavax]). This study aimed to evaluate the association between SARS‐CoV‐2 vaccine class and TM. Methods: This observational, cross‐sectional, pharmacovigilance cohort study examined individual case safety reports from VigiBase, the World Health Organization's pharmacovigilance database. We first conducted a disproportionality analysis with the information component (IC) using the reports of TM that occurred within 28 days following exposure to the FDA or EMA labeled SARS‐CoV‐2 vaccines, from December 1, 2020 (first adverse event related to a SARS‐CoV‐2 vaccine) to March 27, 2022. Second, we analyzed the clinical features of SARS‐CoV‐2 vaccine‐associated TM cases reported in VigiBase. Results: TM was significantly associated both with the messenger ribonucleic acid (mRNA)‐based (n = 364; IC025  = 0.62) and vector‐based (n = 136; IC025  = 0.52) SARS‐CoV‐2 vaccines that are authorized by the FDA or the EMA. Conclusions: Findings from this observational, cross‐sectional pharmacovigilance study showed that mRNA‐based and vector‐based FDA/EMA labeled SARS‐CoV‐2 vaccines can be associated with TM. However, because TM remains a rare event, with a previously reported rate of 0.28 cases per 1 million vaccine doses, the risk–benefit ratio in favor of vaccination against SARS‐CoV‐2 virus remains unchallenged. Rather, this study suggests that clinicians should consider the diagnosis of TM in patients presenting with early signs of spinal cord dysfunction after SARS‐CoV‐2 vaccination. ANN NEUROL 2022;92:1080–1089